ANALISIS PENGARUH SHIP’S CALL, INFLASI, TARIF BONGKAR MUAT TERHADAP MUAT G.C KAPAL INTERINSULER DI TANJUNG PERAK - Herman Budi Sasono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
Inter-Island transportation support the links for various goods delivery and the availability of commodities among islands throughout Indonesia. When the scarcity of a commodity exists in one island beause of the delay of goods arrival sechedule, the price of the commodity will rise up and inflation rate can also increase. Therefore, this research investigates the influence of some internal and external factors: unit ship’s call (X1), DWT ship’s call (X2), inflation (X3), and loading-unloading tariff (X4) towards load volume of general cargo (Y) in Tanjung Perak port, Surabaya.And the results are concluded that loading-unloading tariff is influenced strongly with the investigated variables: X1 with regression coefficient by 361.105; X2 with regression coefficient by 0.020; X3 with regression coefficient by 2765.239; and X4 with regression coefficient by 24.854.